Obligasi dan Sukuk Dalam Perspektif Keuangan Islam - Ananda, Qori; Nurul Fatihah Azmi; Qonita Febriani; Gunawan Aji (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to provide a deeper understanding of the basic differences between bonds and sukuk, as well as the implications for Muslim investors in choosing investment instruments that comply with sharia financial principles. The money method used is descriptive-analytical with a qualitative approach to compare bonds and sukuk from a sharia financial perspective. Data was obtained through literature studies from journal literature and official documents related to these two financial instruments. The results of this research are first, although sukuk and bonds are almost similar, if examined more deeply, the two have contradictory characteristics. The main difference is in the use of sharia principles in sukuk while bonds do not. Second, conventional bonds do not require collateral assets, while sukuk must have collateral assets. Third, sukuk is not a debt and receivable instrument that charges interest (riba) like bond transactions, but just like sukuk bonds are part of an investment instrument. Fourth, in terms of offering price, maturity, bond principal at maturity, and rating between sukuk and bonds there is no difference.